How well-intentioned white male physicists maintain ignorance of inequity and justify inaction - Melissa Dancy; Apriel K. Hodari (SpringerOpen, 2023)
Abstract Background We present an analysis of interviews with 27 self-identified progressive white-male physics faculty and graduate students discussing race and gender in physics. White cis men dominate most STEM fields and are particularly overrepresented in positions of status and influence (i.e., full professors, chairs, deans, etc.), positioning them as a potentially powerful demographic for enacting systemic reform. Despite their proclaimed outrage at and interest in addressing inequity, they frequently engage in patterns of belief, speech and (in)action that ultimately support the status quo of white male privilege in opposition to their intentions. Results The white male physicists we interviewed used numerous discourses which support racist and sexist norms and position them as powerless to disrupt their own privilege. We present and discuss three overarching themes, seen in our data, demonstrating how highly educated, well-intentioned people of privilege maintain their power and privilege despite their own intentions: (1) denying inequity is physically near them; (2) locating causes of inequity in large societal systems over which they have little influence; and (3) justifying inaction. Conclusions Despite being progressively minded and highly educated, these men are frequently complicit in racism and sexism. We end with recommendations for helping cis men engage the power they hold to better work with marginalized people to disrupt inequity.